The impact of investigative genetic genealogy: perceptions of UK professional and public stakeholders. (September 2020) - Samuel, G.; Kennett, D.
Highlights: Law enforcement authorities are increasingly employing genealogists to search genetic genealogy databases with unknown origin DNA from unidentified human remains, or from a serious crime scene, to identify the victim or a potential suspected perpetrator. Benefits include increased public safety and bringing justice to victims of crime, and initial public surveys suggest generally positive support. We interviewed 45 predominantly UK public and stakeholder interviews to better understand the underlying reasons for this support, particularly for using these methods during criminal investigations. Support was associated with the extent interviewees perceived the technology as impacting the current use of genetic genealogy databases in terms of individual genealogy database users, the genealogy community, and/or genetic genealogy and law enforcement practices. Abstract: Law enforcement authorities in the United States have been increasingly employing genealogists to search genetic genealogy databases with unknown origin DNA from unidentified human remains, or from a serious crime scene, to identify the victim or a potential suspected perpetrator. There are benefits to this form of searching in terms of public safety and bringing justice to victims of crime, and such searches are legally permissible. However, ethical questions arise regarding whether database users have a reasonable expectation that their DNA information will be searched by law enforcement in this way, and so, in turn, questions about consent and privacy have emerged. While initial surveys suggest generally positive support for using genetic genealogy methods, less work has explored the underlying reasons behind this support. We were interested in exploring the perceptions of key stakeholders in the UK with relation to this, specifically for the purposes of solving serious crimes. Through a series of 45 predominantly UK public and stakeholder interviews, we show a general support for the technology, though interviewees were also able to articulate a range of social and ethical concerns. Support was associated with the extent interviewees perceived the technology as impacting the current use of genetic genealogy databases in terms of individual genealogy database users, the genealogy community, and/or genetic genealogy and law enforcement practices. We present our findings and discuss their implications.